2004
DOI: 10.1162/089892904323057326
|View full text |Cite
|
Sign up to set email alerts
|

Event-related Brain Potentials Elicited by Morphological, Homographic, Orthographic, and Semantic Priming

Abstract: The morphological structure of words, in terms of their stem morphemes and affixes, could influence word access and representation in lexical memory. Three experiments were carried out to explore the attributes of event-related potentials evoked by different types of priming. Morphological priming, with pairs of words related by their stem (hijo/hija [ son/ daughter]), produced a sustained attenuation (and even a tendency to positivity) of the N400 shown by unrelated words across the three experiments. Homogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
61
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 18 publications
(22 reference statements)
15
61
1
Order By: Relevance
“…structure occurs at the orthographic level, with little or no contribution from semantics. Previous ERP research investigating long SOA priming in Spanish had given some support to this idea (Dominguez et al, 2004;Barber et al, 2002). These studies found a reduction in the early part of the N400 component of target recognition that was equivalent for stem homograph pairs (which had an apparent morphological relationship) and transparent morphological pairs.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…structure occurs at the orthographic level, with little or no contribution from semantics. Previous ERP research investigating long SOA priming in Spanish had given some support to this idea (Dominguez et al, 2004;Barber et al, 2002). These studies found a reduction in the early part of the N400 component of target recognition that was equivalent for stem homograph pairs (which had an apparent morphological relationship) and transparent morphological pairs.…”
Section: Discussionmentioning
confidence: 94%
“…Like Rastle et al (2004), we compared masked priming effects for semantically transparent pairs (e.g., darkness-DARK ), semantically opaque pairs (e.g., corner-CORN ), and nonmorphological form pairs (e.g., brothel-BROTH). Based on the suggestive findings of Dominguez et al (2004) and Barber et al (2002), our expectation was that the semantically transparent and semantically opaque primes would yield equivalent attenuation of the N400 component in response to their respective targets (relative to unrelated control primes), and that this reduction in the N400 component would be greater than that yielded by nonmorphological form primes. The pattern of data predicted in this study would constitute the first unambiguous neurophysiological evidence for a form of morphological decomposition that is insensitive to semantic information.…”
Section: Using Erps To Examine Morphological Analysismentioning
confidence: 91%
See 2 more Smart Citations
“…This component is a negative wave with an onset latency between 200 and 250 ms post-stimulus, with maximum amplitude at around 400 ms. This wave has been related to semantic processing, since its amplitude is enhanced with semantic incongruence between word and context (Kutas and Hillyard, 1980;Neville et al, 1986) and decreases in conditions in which the context enables the subject to predict the word (Holcomb and Neville, 1991) or when semantically related stimuli have previously been presented (Bentin, 1987;Bentin et al, 1985;Holcomb, 1988;Kutas and Van Petten, 1988;Holcomb and Neville, 1990;Dominguez et al, 2004;Kiefer, 2005). The presence of the N400 has also been tested in studies in which nonverbal materials are used, and, just as with words, semantic priming in picture processing tasks decreases the amplitude of this component (Barrett and Rugg, 1990;McPherson and Holcomb, 1999).…”
Section: Introductionmentioning
confidence: 99%